Role of Receptor for Advanced Glycation End Products in Regulating Lung Fluid Balance in Lipopolysaccharide-induced Acute Lung Injury and Infection-Related Acute Respiratory Distress Syndrome. Issue 4 (October 2018) - Wang, Hao; Wang, Tao; Yuan, Zhicheng; Cao, Yufang; Zhou, Yongfang; He, Junyun; Shen, Yongchun; Zeng, Ni; Dai, Luqi; Wen, Fuqiang; Chen, Lei
Abstract : ABSTRACT: Receptor for advanced glycation end products (RAGE) is implicated in inflammatory responses in acute lung injury (ALI)/acute respiratory distress syndrome (ARDS), but its role in pulmonary edema formation remains unclear, especially in infection-related ARDS mainly caused by pneumonia or sepsis. In this study, we investigated the role of RAGE in alveolar fluid regulation by using RAGE gene knockout ( RAGE −/− ) mice in a murine ALI model induced by lipopolysaccharide (LPS), and by comparing soluble RAGE (sRAGE) levels in serum and bronchial alveolar lavage fluid between ARDS patients and control subjects. We found that RAGE knockout significantly improved alveolar fluid clearance and reduced pulmonary vascular albumin leakage upon LPS challenge. Furthermore, LPS-induced substantial decrease in lung expression of sodium–potassium ATPase (Na, K-ATPase), epithelial sodium channel, and zonula occluden-1 (ZO-1) were fully or partially restored by the deletion of RAGE. In addition to this, LPS-induced lung leukocyte infiltration and inflammatory cytokine and chemokine release were all attenuated in RAGE −/− mice as compared to wide-type mice. In infection-related ARDS patients, both serum and bronchial alveolar lavage fluid levels of the sRAGE were much higher than those in control subjects, and they were positively correlated with pulmonary vascular permeability and levels of interleukin (IL)-6, IL-8, and macrophage inflammatory protein (MIP)-2. Taken together, we provided the first direct evidence for the essential role of RAGE in regulating lung fluid balance in infection-related ARDS/ALI. The underlying mechanisms may involve the downregulation of both ion-channel and tight junction proteins mediated by RAGE signaling in bacterial endotoxin-induced lung injury. Abstract : Supplemental Digital Content is available in the text